Dendritic spine loss deep in the neocortex and dendrite distortion with diffusion disturbances occur early in experimental pneumococcal meningitis - Baronti, Dario; Tomov, Nikola; Hupp, Sabrina; Mitchell, Timothy J.; Iliev, Asparouh I. (Frontiers in Neuroscience, 2023)
Streptococcus pneumoniae (pneumococcus) meningitis is a serious disease with substantial lethality and long-term disability in survivors. Loss of synaptic staining in the superficial layers of the neocortex in rodent models and in humans, and pneumolysin (a major pneumococcal toxin)-dependent dendritic spine collapse in brain slices have been described. It remains unclear how deep in the neocortex more discrete changes are present, how soon after disease onset these changes occur, and whether other properties of dendrites are also affected. Using a mouse model of pneumococcal meningitis, we studied changes in the neocortex shortly (3-6 h) after the onset of clinical symptoms via modified Golgi-Cox silver staining. Dendritic changes were present in areas with otherwise unchanged cell numbers and no signs of necrosis or other apparent neuronal pathology. Mature dendritic spines were reduced in the pyramidal neurons running through layers 1 to 5. Additionally, spine morphology changes (swelling, spine neck distortion), were also observed in the deeper layers 4 and 5 of the neocortex. Immature spines (filopodia) remained unchanged between groups, as well as the dendritic arborization of the analyzed neurons. In a third of the animals with meningitis, massive mechanical distortion of the primary dendrites of most of the pyramidal neurons through layers 1 to 5 was observed. This distortion was reproduced in acute brain slices after exposure to pneumolysin-containing bacterial lysates (S. pneumoniae D39 strain), but not to lysates of pneumolysin-deficient bacteria, which we explain by the tissue remodeling effect of the toxin. Experimental mechanical dendrite distortion in primary neural cultures demonstrated diminished FRAP diffusion of neuronally-expressed EGFP, indicative of disturbed dendritic diffusion. Our work extends earlier knowledge of synaptic loss in the superficial cortical layers during meningitis to deeper layers. These changes occurred surprisingly early in the course of the disease, substantially limiting the effective therapeutic window. Methodologically, we demonstrate that the dendritic spine collapse readout is a highly reliable and early marker of neural damage in pneumococcal meningitis models, allowing for reduction of the total number of animals used per a group due to much lower variation among animals.